Boric compounds as food preservatives
1926-06 1926 1920s 8 pages - 4 - agreed that certain preservatives, for example, sulphurous acid, allow decomposition to occur, but mask the odour of putrefaction, there is no agreement amongst the experts that this applies to boric compounds. Experiments by Prof. Eyre (Morning Post, March 2nd. 1925) show that boric acid does not mask the physical signs of noxious change. In 1912 the addition of any preservative, including boric compounds, to milk was made illegal (The Public Health Milk and Cream Regulations, 1912). By the same Regulations preserved cream may not contain any preservative, save boric acid, borax, or hydrogen peroxide. Thus all other preservatives, including benzoic acid, were ruled out, presumably because they were considered more objectionable than boric compounds. As the majority of physicians and physiologists appear to disapprove of the use of preservatives on general grounds, the Government are justified in forbidding the use of them where better methods of preservation are known; but in the Public Health (Preservatives, etc, in Food) Regulations, 1925, benzoic acid and sulphurous acid are permitted, and boric compounds prohibited. We have every reason to believe that the Departmental Committee appointed by Mr. Chamberlain in 1923 sifted a great mass of evidence, and reached their decisions with great care and deliberation, but it is difficult to understand how they could arrive at this conclusion from such researches as have been published. One concludes that they were supplied with a considerable amount of new material, and we think the Government ought to be asked to publish the evidence, so that all could know the established scientific facts on which the conclusions were based. (b) Research Work The most important researches which have been publishes on the effect of boric compounds on the human system are as follow :- 292/840/1/3